Engineering Wonders: The Golden Gate Bridge - Stanborough, Rebecca (North Mankato, Minnesota Capstone Press, 2016)
"Explains the history behind and the process of building the Golden Gate Bridge"--Provided by the publisher.
Keywords: Bridges -- California; San Francisco; Design and construction; Juvenile literature; Golden Gate Bridge (San Francisco, Calif.) -- Juvenile literature; Golden Gate Bridge (San Francisco, Calif.) -- Design and construction; History; Juvenile literature